Sexual Behaviors, Mobile Technology Use, and Sexting Among College Students in the American South. Issue 1 (January 2019) - Ingram, Lucy A.; Macauda, Mark; Lauckner, Carolyn; Robillard, Alyssa
Purpose: To examine sexual, mobile technology, and sexting behaviors of college students. Design: A cross-sectional study design was employed. Setting: Study sites were 2 universities in the southern United States. Subjects: Data were collected from 254 participants via online survey of college students. Measures: The survey included 268 items inclusive of measures from previously validated sources. Variables for this study included technology ownership/use, online/mobile dating site use, sexting behaviors/attitudes, and sexual behaviors. In particular, the Sexting Attitudes Scale has been previously validated with other researchers providing comparative data. Analysis: Chi-square and Mann-Whitney tests were used for group comparisons. Logistic regression analysis was used to examine predictors of sexting behavior. Results: Of the 254 participants, over 80% had ever had sex, and participants were more likely to use condoms with partners who they were not in a committed relationship compared to those to whom they were committed (χ 2 = 27.324, P = .0001). Seventy percent had ever sexted, and sexting attitudes ranged from approximately 80% agreeing that sexting is "risky" or can leave one "vulnerable" compared to 43% agreeing that sexting is "fun." Sexting was associated with having multiple sexual partners (odds ratio [OR] = 2.47, 95% confidence interval [CI]: 1.36-4.47) and sexually transmitted infection testing history (OR = 2.08, 95% CI: 1.03-4.18). Conclusion: Study findings should be considered as interventionists plan sexual health and risk prevention programs for college students.